PENINGKATAN KETERAMPILAN MEMBACA INTENSIF MENGGUNAKAN MODEL COOPERATIVE SCRIPT KELAS VIA SDN 09 KOTO LUAR KOTA PADANG - putri, hasnatul; mahyuddin, ritawati; abidin, zainal (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at describing the improvement of students’ skill intensive reading by using the “Cooperative Script” at class VIA SDN 09 Koto Luar, Padang. The subjects were the teachers and twenty five students of class VI A. This class action research applied both qualitative and quantitative approaches. It was conducted in two cycles. The research result show that there are some improvements. As a whole, their score enhanced from 68,9% in cycle I to 91,5% in cycle II. First, their score in the Pre-reading activity increased from 76% in cycle I to 93% in cycle II. Second, their score in the Whilst-reading activity enhanced from 61% in cycle I to 91% in cycle II. Third, the score increased in post-reading activity from 69,65% in cycle I to  90,5% in  cycle  II.  Thus,  it  is concluded  that  the  the  Cooperative  Script  modelsuccessfully improves students’ skill in intensive reading.                                                                                   Keywords: intensive reading skill, the “coopative script model”